Effects of adding convalescent plasma therapy for treatment of COVID-19 patients with severe and critical symptoms: a descriptive study of 12 cases - Sali, Shahnaz; Tehrani, Shabnam; Lotfali, Ensieh; Yadegarynia, Davood; Abolghasemi, Sara (Novelty in Biomedicine, 2021)
Background: Severe symptoms of COVID-19 could be actually life-threatening and fatal. No effective treatment has been proposed yet. Plasma from COVID19 recovered patients may be effective according to past similar studies of some other viral infections. Materials and Methods: This study was conducted at the infectious disease ward of Shahid Labbafi Nejad Hospital (Tehran, Iran) from 3rd of April 2020 up until 3rd of May 2020. Clinical information for the 12 patients, before and after receiving convalescent plasma transfusion was obtained from a review of the hospital computer medical system retrospectively and analyzed. Results: Out of 12 patients with Covid-19 who received convalescent plasma, 7 patients were male (58.3%) and 5 were female (41.7%). The mean age of the patients was 52 years. Among them, 50% (n=6), improved and discharged and the rest of them died. Mean O2 saturation of patients with final outcome of death and discharged before plasma therapy were 67 (33%) and 77 (83%), respectively, an improvement, defining partial resolution of lesions of chest CT scan or stop in progression of infiltrations was detected in all of 6 discharged patients. Conclusion: Convalescent plasma may have effective role in improving O2 saturation, lymphopenia and CT scan lesions and also decreasing inflammatory factors of cases with severe manifestations but could not change prognosis for critically ill patients. Therefore, an early administration of convalescent plasma may be helpful.